2004
DOI: 10.1021/jf049477a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Nature and Aroma Compound Hydrophobicity on Flavor Release from Complex Food Emulsions

Abstract: Complex food emulsions containing either hydrogenated palm kernel oil (vegetable fat) or anhydrous milk fat (animal fat) were flavored by using different aroma compounds. The fats differed by their fatty acid and triacylglycerol compositions and by their melting behavior, while the aroma compounds (ethyl butanoate, ethyl hexanoate, methyl hexanoate, mesifurane, linalool, diacetyl, cis-3-hexen-1-ol, and gamma-octalactone) differed by their hydrophobicity. Application of differential scanning calorimetry to fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…Starch can bind some aroma compounds (Arvisenet et al 2002;Seuvre et al 2006;van Ruth and King 2003) and many cereal foods also contain significant amounts of fat, which affects partition (Ingham et al 1996). Therefore, the pattern of aroma release in vitro and in vivo can change (Brauss et al 1999;Miettinen et al 2004;Relkin et al 2004). The structure of the solid food is also related to sensory attributes like crispness, hardness, and crumbliness which may affect perceived flavor through crossmodal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Starch can bind some aroma compounds (Arvisenet et al 2002;Seuvre et al 2006;van Ruth and King 2003) and many cereal foods also contain significant amounts of fat, which affects partition (Ingham et al 1996). Therefore, the pattern of aroma release in vitro and in vivo can change (Brauss et al 1999;Miettinen et al 2004;Relkin et al 2004). The structure of the solid food is also related to sensory attributes like crispness, hardness, and crumbliness which may affect perceived flavor through crossmodal interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The change in bulk polarity will reduce the airproduct partition coefficient of hydrophobic compounds and therefore will reduce the concentration of total volatile compounds in the headspace. There will be a compoundspecific effect that is driven by polarity, although this has not been further detailed as this study is not solely focused on the static partitioning of volatile compounds, a topic that is well covered by previous authors [14,19,[45][46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…For example, emulsions prepared with linseed oil (rich in unsaturated fatty acids) are more able to retain allylisothiocyanate than emulsions prepared with other commercial oils, such as olive sunflower or rapeseed oils (Guichard, 2002). A comparison between animal and vegetable oils showed that esters were better released from emulsions prepared with vegetable oil, which was explained by the lower proportion of liquid fat in the vegetable oil and a lower proportion of soluble proteins able to bind these aroma compounds (Relkin et al, 2004).…”
Section: Emulsionsmentioning
confidence: 99%